Effectiveness of red palm oil supplementation on motor impairment in a Paraquat-induced Parkinsons disease rat mode - Siregar, Ari Ramadhan; Ichwan, M; Siregar, Jelita; Anggraini, Dwi; Hasibuan, Hasrul (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Parkinson's is a neurological disease that is rapidly increasing to surpass Alzheimer's disease. Parkinson's disease causes a decrease in the number of dopaminergic neurons, which can lead to disturbances in attention, memory, and motivation. Damage to dopaminergic nerve cells is caused by increased free radicals (ROS) levels in tissues and cells, thus inducing cell death signals. This study aims to determine whether red palm oil affects the acute level of Parkinson's syndrome in rats induced with paraquat. This study uses the BEAM and Cylinder tests to measure the effect of red palm oil because one of the alternative therapies for neurodegenerative illnesses like Parkinson's is red palm oil. The treatment was administered to paraquat-induced rats with injections given weekly for four weeks. Carotenoids are present in red palm oil at concentrations of 600 to 1000 ppm and are thought to have neuroprotective properties. As many as 30 rats were divided into three groups: K (control), PQT (paraquat 7 mg/kg body weight), and PQT+MSM (paraquat 7 mg/kg body weight + 2 ml of red palm oil). The data were then checked using the normality test Shapiro-Wilk and analyzed statistically using One-way ANOVA. The Cylinder and Beam tests were significant, with a P value of 0.00. Parkinsonian rats receiving red palm oil at a dose of 2 ml/kg body weight per week for four weeks showed improved motor function compared to those receiving only paraquat. The group with red palm oil had a lower beam test value. This indicates motor improvement in Parkinson's model rats. Similarly, the cylinder test showed higher performance in the group treated with red palm oil. Based on this, it can be concluded that red palm oil influences the motor movements of Parkinson's rats. The beam test and cylinder test methods prove this. Red palm oil could decrease the acute level of motor impairments in rats with Parkinson's induced by paraquat.